Self-Esteem Among Child Sexual Abuse Victims: A Study In Ernakulam District, Kerala - Cherian, Tania; Sukumaran, N (Journal of Neonatal Surgery, 2025)
The study investigates the psychosocial rehabilitation of child sexual abuse victims in Ernakulam District, Kerala, with a specific focus on self-esteem. The primary objective is to assess the level of self-esteem among victims and examine its variation based on socio-demographic factors, including monthly family income, type of family, and duration of shelter home stay. Adopting a descriptive research design, primary data were collected from 263 survivors (aged 18–25) through structured interview schedules. A purposive sampling method was employed, targeting individuals whose abuse occurred between ages 13 and 17. Self-esteem was measured using a 14-item five-point Likert scale (Cronbach’s Alpha = 0.91). Data analysis involved descriptive statistics, t-tests, and ANOVA. The findings reveal that 50% of victims have high self-esteem (Mean = 4.5786), 28.57% moderate (Mean = 3.4480), and 21.43% low (Mean = 2.7807). Significant differences in self-esteem were found based on monthly family income (F = 15.688, p < 0.05), family type (t = 3.301, p < 0.05), and shelter stay duration (F = 2.807, p < 0.05). The study highlights the need for tailored rehabilitation programs addressing economic, social, and environmental influences on recovery.